Lipid nanoparticle-encapsulated DNA vaccine robustly induce superior immune responses to the mRNA vaccine in Syrian hamsters - Hung-Chun Liao; Kuan-Yin Shen; Chung-Hsiang Yang; Fang-Feng Chiu; Chen-Yi Chiang; Kit Man Chai; Wan-Chun Huang; Hui-Min Ho; Yi-Hua Chen; Min-Syuan Huang; Ching-Len Liao; Hsin-Wei Chen; et al. (Molecular Therapy: Methods & Clinical Development, 2024)
DNA vaccines for infectious diseases and cancer have been explored for years. To date, only one DNA vaccine (ZyCoV-D) has been authorized for emergency use in India. DNA vaccines are inexpensive and long-term thermostable, however, limited by the low efficiency of intracellular delivery. The recent success of mRNA/lipid nanoparticle (LNP) technology in the coronavirus disease 2019 (COVID-19) pandemic has opened a new application for nucleic acid-based vaccines. Here, we report that plasmid encoding a trimeric spike protein with LNP delivery (pTS/LNP), similar to those in Moderna’s COVID-19 vaccine, induced more effective humoral responses than naked pTS or pTS delivered via electroporation. Compared with TSmRNA/LNP, pTS/LNP immunization induced a comparable level of neutralizing antibody titers and significant T helper 1-biased immunity in mice; it also prolonged the maintenance of higher antigen-specific IgG and neutralizing antibody titers in hamsters. Importantly, pTS/LNP immunization exhibits enhanced cross-neutralizing activity against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants and protects hamsters from the challenge of SARS-CoV-2 (Wuhan strain and the Omicron BA.1 variant). This study indicates that pDNA/LNPs as a promising platform could be a next-generation vaccine technology.